Failure Analysis of Fuel System Main Engine Fishing Vessel (Case Study : KM. Sumber Mutiara) - Rizqi Ilmal Yaqin; Mohamad Akmal; Juniawan Preston Siahaan; Mega Lazuardi Umar; Bambang Hari Priyambodo; Yuniar Endri Priharanto (Department of Naval Architecture - Diponegoro University, 2023)
Failure analysis on the fishing vessel's main engine is one of the works that must be completed because it is crucial for the operation of the ship. Analysis of determining the cause and effect of the failure main engine fuel system is the goal of this study. FMEA (Failure Mode and Effect Analysis) is a method used to determine priority components in failure. The use of Pareto diagrams is an additional method of analysis. RCFA (Root Cause Failure Analysis) is used to analyze the root cause of the failure of the main engine fuel system. The results obtained are the injector component (168) is the component that has the highest RPN value and is the largest contributor to failure according to the Pareto diagram. The root of the failure identified is the lack of checking before operating. The results of the recommendations obtained are the use of corrective maintenance based on the RPN value and the use of a clean filter for the fuel system. The injector is a component that needs to be maintained so as not to experience a fuel system failure on the main engine. The impact of the results of this study is that it becomes a scientific finding using FMEA and RCFA as a method of analyzing failures in the main engine fuel system on fishing vessels